Larval Fish Composition, Distribution and Diets in the Seagrass-Mangrove Ecosystem of Gelang Patah, Johor, Malaysia - Ara, Roushon (2011)
Fish larval composition, spatio-temporal distribution, density, family richness, Shannon-Wiener index and feeding habits were determined by analyzing samples collected from the seagrass-mangrove ecosystem of Gelang Patah, Johor Strait, Peninsular Malaysia between October 2007 and September 2008. Five stations were selected namely Upper estuary (S1), middle estuary (S2) and lower estuary (S3) of Pendas River; seagrass beds (S4) and open seas (S5). Each sampling station was approximately 1 km apart from each other. Fish larvae were collected by subsurface towing of bongo net equipped with a flow meter. In total, 24 families of fish larvae belong to six orders were identified from seagrass-mangrove ecosystem of Gelang Patah, Johor Strait. Similarity matrix and cluster analysis revealed that there are six different families under the order Perciformes. In total, 24 families were identified from the coastal waters of Gelang Patah, Johor, Peninsular Malaysia. Among them, 14 occurred in upper estuary, 17 in middle estuary, 16 in lower estuary, 20 in seagrass beds and 16 in open sea. Overall five (Clupeidae, Blenniidae, Terapontidae, Gobiidae and Sillaginidae) were the most dominant in study areas. Shannon-Wiener index varied significantly within monsoon and intermonsoon seasons peaking in the months October-January and May-August. The highest density of larval fishes was recorded at seagrass station (S4) and the spatial variations in larval density were significant (p < 0.05) between seagrass and other four sampling sides. None of the diversity indices showed significant among-stations except only family richness was significantly (p < 0.05) higher in seagrass beds than upper estuary. Among 24 families, 18 families were found to have correlation either positively or negatively with the water parameters. The highest and significant regression coefficient was observed in Sillaginidae which indicated 72% abundance of Sillaginidae was influenced by the major water parameters and remaining 28% by other factors. In total, 267 Blenniidae, 401 Clupeidae, 126 Gobiidae and 117 Terapontidae stomachs were examined during the study period. Analyses of prey in the stomachs identified 24 important items (%Rs > 0.05) belonging to six major groups: phytoplankton, zooplankton, algae, plant like matter, debris and unidentified materials. According to the Simple Resultant Index (%Rs), the predominant food item in the stomach of all four families (Blenniidae, Clupeidae, Gobiidae and Terapontidae) was phytoplankton (> 60%). This was followed by zooplankton in Blenniidae (18.24%) and Clupeidae (8.60%). On the other hand, the second diet composition was plant like matter in Gobiidae (14.73%) and Terapontidae (8.02%). Among phytoplankton, Dacytyloccopsis fasicularis (26.31%) was large quantity in the stomachs of Bleniidae and this was followed by Nitzschia baccata (23.38%). Conversely, Nitzschia sp. was the highest quantity (26.33%) in the stomachs of Clupeidae larvae and subsequently Dacytyloccopsis fasicularis (13.56%), Biddulphia sinensis (10.51%), Rhizosolenia araturensis (8.63%), Lauderia borealis (8.06%) and Fragilaria intermedia (3.47%). In Gobiidae larvae, Chromophyta (28.30%) was observed as the highest quantity and second highest component was Nitzschia sp. (15.97%) and then Dacytyloccopsis fasicularis (8.27%). Similarly, Chromophyta (29.12%) was the highest quantity in the stomachs of Terapontidae (Table 6.17). Second and third component was Nitzschia sp. (15.95%) and Dacytyloccopsis fasicularis (13.80%). Overall, two most dominant phytoplankton (Dacytyloccopsis fasicularis and Nitzschia sp.) was observed among the four larval families. It is revealed that various food items were found in the stomachs of Bleniidae, Clupeidae, Gobiidae and Terapontidae larvae and remarkable that phytoplankton were more than 60% in the diet composition. Therefore, all studied fish larval families in the study areas are exclusively herbivore.